2012
DOI: 10.12968/jowc.2012.21.9.457
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cutaneous wound healing by silymarin in rats

Abstract: There were no external sources of funding for this study. The authors have no conflicts of interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 25 publications
1
51
0
Order By: Relevance
“…This method of wound induction has been used previously to investigate cutaneous wound healing in rats. 35 …”
Section: Wound Creationmentioning
confidence: 99%
See 1 more Smart Citation
“…This method of wound induction has been used previously to investigate cutaneous wound healing in rats. 35 …”
Section: Wound Creationmentioning
confidence: 99%
“…The data were then multiplied by 7.46 to convert them from hydroxyproline content to collagen content. 35,40 Glycosaminoglycans content Content of Glucosamine (GLA) and galactosamine (GAA), as indices of tissue glycosaminoglycans (GAGs), were analysed according to the methods of Ohkuma et al 41 Briefly, 10 mg of the freeze-dried tissue sample was diluted in 2 mL of 1N HCl and incubated at 120°C, to produce hydrolysed and dried tissue. Phosphate buffer saline (0.5 mL; pH 7) and 1 mL 4N NaCl were added to the hydrolysed sample.…”
Section: Determination Of the Collagen Contentmentioning
confidence: 99%
“…The results of analysis of inflammatory cells (lymphocytes, macrophages and neutrophils) indicated that AgNPs@ Falcaria ointment regulated significantly ( p ≤ 0.01) the number of these cells at day 10 compared to the other groups (Table ). Macrophages are the most important cells in the inflammatory stage that contribute to elimination of necrotic tissues and bacteria . These cells also contribute to the localization of inflammation process and absorption of fibroblasts to initiate proliferation by releasing some chemotoxic factors.…”
Section: Resultsmentioning
confidence: 99%
“…Large numbers of healing agents have been extensively tested in the literature with beneficial outcomes [3][4][5][6][7][8][9][10][11][107][108][109][110][111][112][113][114][115]. Honey and aloe Vera have been used for skin wound healing and have shown that they can modulate inflammation and increase collagen production and aggregation [110,114].…”
Section: Healing Promotive Factorsmentioning
confidence: 99%
“…Tarantula cubensis has also been shown to regulate different stages of inflammation in order to increase the healing response at further stages of tendon healing [8,11]. Garlic and sylimarin has been shown to be anti-inflammatory and antioxidant agents who their effectiveness on wound healing have been extensively described [115,116]. Several other agents such as vitamin C, non-steroidal anti-inflammatory agents such as indomethacin and celecoxib have been shown to regulate the inflammation and are effective in the healing quality [1,117,118].…”
Section: Healing Promotive Factorsmentioning
confidence: 99%